Correction to: Late initiation of antiretroviral therapy: inequalities by educational level despite universal access to care and treatment - Amanda Rodrigues; Claudio J. Struchiner; Lara E. Coelho; Valdilea G. Veloso; Beatriz Grinsztejn; Paula M. Luz (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.